2020
DOI: 10.1002/nme.6550
|View full text |Cite
|
Sign up to set email alerts
|

A note on the accuracy of the generalized‐α scheme for the incompressible Navier‐Stokes equations

Abstract: We investigate the temporal accuracy of two generalized-schemes for the incompressible Navier-Stokes equations. In a widely-adopted approach, the pressure is collocated at the time step t n + 1 while the remainder of the Navier-Stokes equations is discretized following the generalized-scheme. That scheme has been claimed to be second-order accurate in time. We developed a suite of numerical code using inf-sup stable higher-order non-uniform rational B-spline (NURBS) elements for spatial discretization. In doin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 37 publications
(78 reference statements)
2
26
0
Order By: Relevance
“…Evaluating pressure at t n+α f recovers second-order accuracy for the overall algorithm, simplifies the implementation, and resolves a troubling issue in geometric multiscale modeling. Interested readers are referred to [49] for details.…”
Section: Fully Discrete Formulationmentioning
confidence: 99%
“…Evaluating pressure at t n+α f recovers second-order accuracy for the overall algorithm, simplifies the implementation, and resolves a troubling issue in geometric multiscale modeling. Interested readers are referred to [49] for details.…”
Section: Fully Discrete Formulationmentioning
confidence: 99%
“…We additionally emphasize novel aspects of our numerical strategy pertaining to the temporal discretization and linear solver. Temporal discretization of the entire FSI system is performed with the generalized-α scheme, in which velocity and pressure are uniformly evaluated at the intermediate time step to achieve uniform second-order temporal accuracy, in direct contrast to the predominant dichotomous approach offering only first-order accuracy of pressure [4]. Furthermore, block preconditioning of a monolithically coupled FSI system is made possible for the first time through a segregated predictor multi-corrector algorithm preserving the block structure of the incompressible Navier-Stokes equations in the implicit solver's fully consistent linear system.…”
Section: Discussionmentioning
confidence: 99%
“…The generalized-α method is applied for temporal discretization of the semi-discrete FSI formulation derived in Section 2.2, in which both velocity and pressure are collocated at the intermediate time step to achieve uniform second-order temporal accuracy [4]. Without loss of consistency, the fully discrete scheme is solved with a segregated predictor multi-corrector algorithm preserving the two-by-two block structure of the incompressible Navier-Stokes equations in the implicit solver's associated linear system.…”
Section: Solution Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that conventionally the pressure field is evaluated at the (n + 1) st time step rather than the (n + α f ) th time step. However, as recently shown in [38], this limits the accuracy of the pressure field to first-order-in-time. Moreover, we have found that evaluating the trace fields at the (n + 1) st time step rather than the (n + α f ) th time step limits the accuracy of all fields to first-order-in-time.…”
Section: Fully-discrete Hdg Formulation For the Mhd Equationsmentioning
confidence: 96%